2021
DOI: 10.1039/d1me00008j
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun polyacrylonitrile/2-(acryloyloxy)ethyl ferrocenecarboxylate polymer blend nanofibers

Abstract: Ferrocene (Fc)-containing monomers were synthesized from ferrocene carboxylic acid and 2-hydroxyethyl acrylate as precursors, and the synthesized monomer was polymerized with ethyl 2-bromoisobutyrate by the atom transfer radical polymerization (ATRP)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…13). 81–84 The initial resistance is the solution resistance ( R s ), which is equal to the total of the electrolyte and modified film and substrate electrical resistances. The modified film capacitance is provided by Q , which is a parallel connection with the R ct element.…”
Section: Resultsmentioning
confidence: 99%
“…13). 81–84 The initial resistance is the solution resistance ( R s ), which is equal to the total of the electrolyte and modified film and substrate electrical resistances. The modified film capacitance is provided by Q , which is a parallel connection with the R ct element.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a crystalline-to-amorphous transition takes place with the addition of CNTs into SBS/PStyr, evidencing that the crystallization is retarded. The XPS results concluded that the major structural, thermal and morphological changes happen with the addition of CNTs to the SBS/PStyr sample due to the increase in the C1s sp 2 and decrease in the C1s C-O, CO and OCO peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Electrospinning exhibits a unique ability to produce diverse forms of polymeric fibrous assemblies. [1][2][3] The remarkable specific surface area and high porosity make electrospun nanomaterials highly attractive as ultrasensitive sensors and of increasing importance in other nanotechnological applications. [4][5][6][7][8] Electrospun polymer nanofibers can be used in sensor applications as their effective sensing surface area increases with decreasing fiber diameter.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Electrospun nanofibers of polymers and polymeric composites are very important for bone tissue engineering and drug release patches. In tissue engineering applications, 4–7 a highly porous polymeric scaffold is required to permit the diffusion of nutrients from the scaffold as cells grow, as well as to accommodate and direct their growth. Electroactive porous membranes with improved homogeneously dispersed particles, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Electrospun nanofibers of polymers and polymeric composites are very important for bone tissue engineering and drug release patches. In tissue engineering applications, [4][5][6][7] a highly porous polymeric scaffold is required to permit the diffusion of nutrients from the scaffold as cells grow, as well as to accommodate and direct their growth. Electroactive porous membranes with improved homogeneously dispersed particles, i.e., iron oxidecontaining (conductive polymer) poly(m-anthranilic acid) (P3ANA)/polycaprolactone (PCL), can be a good candidate as a potential bioelectronic porous membrane material for electrochemical immunosensors.…”
Section: Introductionmentioning
confidence: 99%